Sedentism and Mobility in a Social Landscape : Mesa Verde and Beyond - Varien, Mark (Book collections on Project MUSE., 1999)
Varien's research clearly demonstrates the need to view agriculturalists from a perspective that differs from the hunter-gatherer model. This innovative study shows why current explanations for site abandonment cannot by themselves account for residential mobility and offers valuable insights into the archaeology of small-scale agriculture.